Pengaruh Model Cooperative Learning Tipe Think Pair Share Terhadap Kemampuan Membaca Siswa Kelas V SDN Kloposepuluh 2 Sidoarjo - Handika Dony Rahmadani; Fachrur Rozie (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This research aims to determine whether or not there is an effect of the Think Pair Share Type Cooperative Learning Model on the Reading Ability of Class V Students at Sdn Kloposepuluh 2 Sidoarjo. This research is a quantitative research with a pre-experimental design, then using the One-Group Pre-test–Post-test Design type. The sampling technique in this research is non-probability sampling consisting of all class V students at SD Negeri Kloposepuluh 2 Sidoarjo. The instruments used in this research first went through a validity and reliability testing process to find out whether they were suitable for use or not. The prerequisite test used here is the normality test. The hypothesis test used in this research is the paired sample t-test. All tests were calculated with the help of IBM SPSS 24. Based on the results of the t-test data analysis, it was found that the value of tcount > ttable (11.611 > 1.699) and the value of Sig. (2-tailed) < 0.05 (0.000 < 0.05) which means Ho is rejected and Ha is accepted which means there is a difference between the pretest and posttest results. So it can be concluded that there is an influence on the application of the Think Pair Share Type Cooperative Learning model on the Reading Ability of Class V Students at Sdn Kloposepuuh 2 Sidoarjo.